Analisis Tes Usabilitas Menggunakan Metode Eye Tracking Pada Website Mahasiswa - Carissa Puspa Maychaela; Ina Siti Hasanah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Gunadarma University campus has various websites. One of the websites owned by Gunadarma University is the studentsite. The studentsite website has been designed as well as possible but this website still needs a deeper evaluation so that users who visit the website can feel comfortable. The purpose of this study is to analyze the performance, level of user satisfaction, and the parts that receive the most attention on the Gunadarma University studentsite website. This study uses the eye tracking method and the System Usability Scale (SUS) questionnaire. Based on the results of the study using the eye tracking method, the website performance is still less than optimal because there are still several parts that confuse users on the home page and dashboard. User satisfaction when using the website is relatively low, based on the results of the SUS questionnaire calculation which shows an average score of 53,64 and is categorized as a quality level of F. There are two recommendations for improvement, the first is on the home page, where the login button is moved to the center of the initial display of the website with a arger size and contrasting color. The second recommendation for improvement is on the dashboard, by adding tooltips to make it easier for users to understand the function of each menu or button available. This research can improve the Gunadarma University student website to be better and provide recommendations for web managers to make improvements.